Self-financed Micro-enterprises Under Algerian Law: Concept and Incentives - Lamine, Abdelhamid (Journal of Legal Studies and Researches, 2022)
The Algerian State, in order to promote small and medium-sized enterprises, grants, without discrimination, to self-financed micro-enterprises fiscal incentives, just like those financed by specialized public bodies. These enterprises don’t favor government agencies whose premises are religious and social beliefs. Thus their development will be far from a possible failure, and far from the informal economy.